Thermolabile drug storage in an ambulatory setting - Fernando do Pazo-Oubiña (Nature Portfolio, 2021)
Abstract More thermolabile drugs are becoming available, and in most cases, these medications are dispensed to ambulatory patients. However, there is no regulation once medications are dispensed to patients and little is known with regard to what happens during transport and home storage. Previous studies suggest that these drugs are improperly stored. The present study was designed to determine the storage conditions of thermolabile drugs once they are dispensed to the patient in the Hospital Pharmacy Department. This is a prospective observational study to assess the temperature profile of 7 thermolabile drugs once they are dispensed to ambulatory patients at a tertiary care hospital. A data logger was added to the medication packaging. Temperature was considered inappropriate if one of the following circumstances were met: any temperature record less than or equal to 0 °C or over 25 °C; temperatures between 0–2 or 8–25 °C for a continuous period over 30 min. The time series of temperature measurements obtained from each data logger were analyzed as statistically independent variables. The data shown did not undergo any statistical treatment and must be considered directly related to thermal measurements. One hundred and fourteen patients were included and 107 patients were available for the analysis. On the whole, a mean of 50.6 days (SD 18.3) were measured and the mean temperature was 6.88 °C (SD 2.93). Three data loggers (2.8%) maintained all the measurements between 2 and 8 °C with less than 3 continuous data (< 30 min) out of this range but no data over 25 °C or below or equal to 0 °C. 28 (26.2%) data loggers had at least one measurement below zero, 1 data logger had a measurement greater than 25 °C and 75 (70.1%) were between 0 and 2 °C and/or between 8 and 25 °C for more than 30 min. In conclusion, once dispensed to patients, most thermolabile drugs are improperly stored. Future studies should focus on clinical consequences and possible solutions.